Seminar “Nonlinear Dynamics” - Статья Редакционная (Моделирование и анализ информационных систем, 2014)
The workshop of the Nonlinear Dynamics scientific-educational center continued its work in 2014, focusing on methods of the dynamical system analysis and studies of their behavior. More than 30 talks in the field of scientific-educational center research have been made this year. The talk topics included numerical analysis of traveling waves in the Fisher–KPP equation with delay and simulations of the twophase heat distribution problem using heterogeneous computing architectures. In a number of talks normal and quasi-normal forms of differential equations with several delays were derived and studied, also one talk considered a problem of optimal control of a telescopic manipulator. The selected talk abstracts are presented in this issue of the journal.